Digitising Ciceronian Papyri: Methods and Resources - Maffei, Fernanda (Ciceroniana On Line, 2021)
The aim of this paper is to give an overview of the digital resources available, both subscription-based and free of charge, for the study of Cicero’s papyri. After an overview of the pioneering role of papyrology in the field of digitization, the article reviews databases related to bibliographic research and metadata, explaining their features and how to use them. This is followed by a section devoted to digital images and their use in manuscript editing and description, also dealing with recent tools for image modification for better reading of the text. Finally, the process of digital edition using Papyri.info is described, highlighting how the Leiden+ markup language is easier to use than XML, which is the basis of the process.